2021
DOI: 10.3390/life11030259
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Training and Cardiac Rehabilitation in COVID-19 Patients with Cardiovascular Complications: State of Art

Abstract: Recent scientific literature has investigated the cardiovascular implications of COVID-19. The mechanisms of cardiovascular damage seem to involve the protein angiotensin-converting enzyme 2 (ACE2), to which severe acute respiratory syndrome (SARS) coronavirus-2 (CoV-2) binds to penetrate cells and other mechanisms, most of which are still under study. Cardiovascular sequelae of COVID-19 include heart failure, cardiomyopathy, acute coronary syndrome, arrhythmias, and venous thromboembolism. This article aims t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
61
1
15

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(77 citation statements)
references
References 145 publications
0
61
1
15
Order By: Relevance
“…Some authors highlighted the important role of cardio-pulmonary rehabilitation programmes [27], with exercise training being a powerful tool in physiotherapy, having the capacity to induce significant improvements in the respiratory and CV systems, facilitating the functional recovery of the respiratory musculature and of the cardiac performance, as well as the reduction of the endothelial dysfunction and of thromboembolic complications [28]. Another aspect is the impact of cardio-pulmonary rehabilitation on the functional capacity, quality of life and prognosis [29].…”
Section: Discussionmentioning
confidence: 99%
“…Some authors highlighted the important role of cardio-pulmonary rehabilitation programmes [27], with exercise training being a powerful tool in physiotherapy, having the capacity to induce significant improvements in the respiratory and CV systems, facilitating the functional recovery of the respiratory musculature and of the cardiac performance, as well as the reduction of the endothelial dysfunction and of thromboembolic complications [28]. Another aspect is the impact of cardio-pulmonary rehabilitation on the functional capacity, quality of life and prognosis [29].…”
Section: Discussionmentioning
confidence: 99%
“…In patients with dyslipidemia and previous COVID-19 infection, exercise training can be an important part of cardiac rehabilitation, capable of inducing significant changes in the cardiovascular system and functional in the recovery of endothelial dysfunction and for the containment of thromboembolic complications [35]. Therefore, although several studies have shown that home programs involving low or moderate to vigorous intensity exercises have been shown to be safe and effective for patients with stable cardiovascular disease, care should be taken when prescribing home training for patients at high risk [36][37][38].…”
Section: Discussionmentioning
confidence: 99%
“…A recent review described an exercise-based rehabilitation program, physiotherapy airway clearance techniques, and techniques focused on ventilation and dyspnea management from existed literature and studies in non-COVID-19 patients [71]. However, it lays the foundations for future research to develop exercisebased rehabilitation and guidelines in COVID-19 survivors [72][73][74]. In any case, exercise is a valuable therapeutic approach with various benefits for respiratory, cardiovascular, and musculoskeletal systems, and future guidelines will be important tools for healthcare workers [75][76][77][78].…”
Section: Cardiovascular Rehabilitation and Exercise In Post-covid-19 Eramentioning
confidence: 99%